Die lebensbedrohliche Haglundferse - Tscholl, M. (Sport-Orthopädie - Sport-Traumatologie, 2011)
A professional ice - hockey player underwent annual periodic health. Beside a painful Haglund exostosis on the left heel and lower back pain no medical issues were raised. A few days later, the player was admitted to the intensive care unit due to a staphylococcus aureus sepsis with pulmonary affection, symphysitis, abscess formation in the external obturator and pectineal muscle. The site of entrance was thought to be an infected blister at the heel, without prior clinical signs of lymphangitis. The soft-tissue probes and the blood cultures showed massive infection with staphylococcus aureus. After 4 weeks of intravenous antibiotic therapy, the patient was discharged from the hospital. Besides the life-threatening condition, the player was able to resume playing four months later only.